2005
DOI: 10.1074/jbc.m508377200
|View full text |Cite
|
Sign up to set email alerts
|

The Needle Component of the Type III Secreton of Shigella Regulates the Activity of the Secretion Apparatus

Abstract: Gram-negative bacteria commonly interact with eukaryotic host cells by using type III secretion systems (TTSSs or secretons). TTSSs serve to transfer bacterial proteins into host cells. Two translocators, IpaB and IpaC, are first inserted with the aid of IpaD by Shigella into the host cell membrane. Then at least two supplementary effectors of cell invasion, IpaA and IpgD, are transferred into the host cytoplasm. How TTSSs are induced to secrete is unknown, but their activation appears to require direct contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
239
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(258 citation statements)
references
References 67 publications
19
239
0
Order By: Relevance
“…1C). CdsF does lack the P-(S/D)-(D/N)-P turn, a four-residue ordered-loop region conserved among many other characterized needle proteins (12,30,61). However, this conservation is not complete, and the motif is only partially present, for example, in EscF of E. coli, PscF of Pseudomonas spp., and SsaH from Salmonella SPI-2 (63).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…1C). CdsF does lack the P-(S/D)-(D/N)-P turn, a four-residue ordered-loop region conserved among many other characterized needle proteins (12,30,61). However, this conservation is not complete, and the motif is only partially present, for example, in EscF of E. coli, PscF of Pseudomonas spp., and SsaH from Salmonella SPI-2 (63).…”
Section: Discussionmentioning
confidence: 97%
“…The precise mechanism by which this occurs has not yet been elucidated; however, it has been postulated that a conformational change in the helical arrangement of the needle may be responsible (30). Hence, the detection of CdsF trimers or dimers could reflect an alteration in helical assembly.…”
Section: Vol 190 2008mentioning
confidence: 99%
See 2 more Smart Citations
“…However, T3SSs (and not flagellar systems) undergo host-contact-mediated activation and translocation of effector proteins into host cells, apparently through direct contact of the external distal tip of the apparatus with the host cell (7)(8)(9). The role of the needle has been probed by using mutagenic studies of the needle-subunit proteins from Yersinia and Shigella (10,11). In these systems, point mutations were identified that led to constitutive secretion of effectors and experimentally uninducible needles.…”
mentioning
confidence: 99%